AN ECONOMIC ANALYSIS OF MEAT POULTRY BREEDING PROJECTS AND THEIR PROFIT EFFICIENCY IN IRAQ FOR THE YEAR 2020( WASIT AS A CASE STUDY) - Al-Hachami, I.S.A; AL-Bahadely, F. H. N.; Jbara, Osamah K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This research was aimed to study and analyze the costs, revenues, and profits of meat chicken breeding projects. The study also estimating the random frontier profit function, the profit inefficiency function and profit efficiency which based on cross-sectional data that included 59 projects for raising meat poultry in Waist governorate in 2020.The results of the analysis showed through the descriptive analysis of the cost structure that, the costs of chicks and fodder account for more than 70% of the costs, as well as achieving economic profits for projects. Through the random border profit function, the significance of both the total revenue and the costs of chicks, fodder, medicines, vaccines, and services (water, electricity and fuel) was shown. As for the inefficiency function parameters, they were significant for each proved the age of the breeder, his years of experience, the presence of the veterinarian and the agricultural engineer. As for the efficiency of profits, it was 76%. The researcher recommended the necessity of supporting breeding projects by providing incentives to feed factories and their processors or supporting feeds and private hatcheries to reduce costs and provide training for less experienced breeders and urge them to involve veterinarians and agricultural engineers in supervising broiler projects.